Impact of coloniser plant species on the development of decomposer microbial communities following deglaciation. - Bardgett, Richard D.; Walker, Lawrence R. (Soil Biology and Biochemistry, 2004)
The effects of coloniser plant species on microbial community growth and composition were investigated on recently deglaciated terrain at Glacier Bay, south-east Alaska. Analysis of microbial communities using phospholipids fatty acid analysis (PLFA) revealed that Alnus and Rhacomitrium had the greatest impact on microbial growth, increasing total PLFA by some 6–7 fold relative to bare soil, whereas Equisetum led to a 5.5 fold increase in total PLFA relative to bare soil. These coloniser species also had significant effects on the composition of their associated microbial communities. Rhacomitrium, Alnus, and Equisetum increased bacterial PLFA, a measure of bacterial biomass, relative to bare soil. Rhacomitrium and Alnus also dramatically increased the concentration of the fungal fatty 18:2ω6 in soil relative to bare soil, by 12-fold and 8-fold, respectively. The net effect of the above changes was a significant increase in the ratio of fungal: bacterial fatty acids in soil associated with Alnus and Rhacomitrium, but not Equisetum. Possible reasons for these effects of particular plants on microbial communities are discussed, as is their significance in relation to the development of microbial communities in relatively sterile, recently deglaciated ground.